A student is trying to solve the system of two equations given below:
Equation P: y + z = 6
Equation Q: 3y + 4z = 1
Which of the following is a possible step used in eliminating the y-term?

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

@ LegendarySadist

a. (y + z = 6) ⋅ 4
b. (3y + 4z = 1) ⋅ 4
c. (y + z = 6) ⋅ −3
d. (3y + 4z = 1) ⋅ 3

please help will give medal

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.